Index C-reactive protein predicts increased severity in acute sigmoid diverticulitis - Kechagias A; Sofianidis A; Zografos G; Leandros E; Alexakis N; Dervenis C (Dove Medical Press, 2018)
Aristotelis Kechagias,1,2 Anastasios Sofianidis,1 Georgios Zografos,3 Emmanouel Leandros,3 Nicholas Alexakis,3 Christos Dervenis1 1Department of Surgery, Konstantopouleion Hospital, Athens, Greece; 2Department of Gastrointestinal Surgery, Kanta-Häme Central Hospital, Hämeenlinna, Finland; 3First Department of Propaedeutic Surgery, Hippocratio Hospital, National and Kapodistrian University of Athens, Athens, Greece Purpose: Conservative management is successful in unperforated (Hinchey Ia) acute diverticulitis (AD) and also generally in local perforation or small abscesses (Hinchey Ib). A higher degree of radiological severity (Hinchey >Ib), ie, a larger abscess (>3–4 cm) or peritonitis, commonly requires percutaneous drainage or surgery. Retrospective studies show that high levels of C-reactive protein (CRP) distinguish Hinchey Ia from all cases of minor and major perforations (Hinchey >Ia). The current study aims to evaluate the usefulness of CRP in distinguishing AD with a higher degree of severity (Hinchey >Ib) from cases that can be treated noninvasively (Hinchey Ia/Ib).Methods: Data from consecutive patients with AD were collected prospectively. All underwent computed tomography (CT). Index parameters obtained at the initial evaluation at the emergency unit were analyzed to assess the association with the outcome. The exclusion criteria comprised concomitant conditions that affected CRP baseline levels.Results: Ninety-nine patients were analyzed. Eighty-eight patients had mild radiological grading (Hinchey Ia/Ib) and eleven had severe radiological grading (Hinchey >Ib; median index CRP 80 mg/L vs 236 mg/L, P<0.001). White blood cells, neutrophils/lymphocytes, serum creatinine, serum glucose, generalized peritonitis, generalized abdominal tenderness, urinary symptoms, and index CRP were related to severe disease. Index CRP was the only independent predictor for Hinchey >Ib (P=0.038). The optimal cutoff value calculated by receiver operating characteristic curve analysis was found to be 173 mg/L (sensitivity 90.9%, specificity 90.9%, P<0.001). All patients who underwent radiological drainage or surgery had an index CRP >173 mg/L and Hinchey >Ib.Conclusion: CRP levels >173 mg/L obtained at the initial evaluation at the emergency unit predict major acute complications in AD. These patients commonly require urgent percutaneous drainage or surgical management.Keywords: acute diverticulitis, C-reactive protein, severity prediction, computed tomography